2010
DOI: 10.1109/tns.2010.2053720
|View full text |Cite
|
Sign up to set email alerts
|

Design, Simulation, Fabrication, and Preliminary Tests of 3D CMS Pixel Detectors for the Super-LHC

Abstract: Abstract-The Super-LHC upgrade puts strong demands on the radiation hardness of the innermost tracking detectors of the CMS, which cannot be fulfilled with any conventional planar detector design. The so-called 3D detector architectures, which feature columnar electrodes passing through the substrate thickness, are under investigation as a potential solution for the closest operation points to the beams, where the radiation fluence is estimated to reach 10 16 n eq cm 2 . Two different 3D detector designs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…If this current is normalized to a single pixel, it falls into the range of ~100 pA to ~2.5 nA. The order of the measured leakage current is consistent with the results of TCAD simulations [6]. The experimental breakdown voltages are well above the depletion voltages, being ~100 V for 4E sensors and ~120 V for 2E sensors.…”
Section: A Leakage Current Characteristicssupporting
confidence: 80%
See 2 more Smart Citations
“…If this current is normalized to a single pixel, it falls into the range of ~100 pA to ~2.5 nA. The order of the measured leakage current is consistent with the results of TCAD simulations [6]. The experimental breakdown voltages are well above the depletion voltages, being ~100 V for 4E sensors and ~120 V for 2E sensors.…”
Section: A Leakage Current Characteristicssupporting
confidence: 80%
“…A quite small inefficiency should arise from the charge loss associated with ionizations through the bias columns and readout columns. Simulations have shown that about 60 % of the charge generated within the columns can be collected before irradiation [6]. Given that the electrodes constitute about 4 % of the total detector volume for the 2E configuration, the expected overall efficiency is ~ 98.5%.…”
Section: B Charge Collection Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full 3D pixel sensors compatible with the CMS pixel readout chip have been fabricated by Sintef. 17 The pixel unit cell is 150 µm x 100 µm in size. Two different device configurations have been investigated: four junction columns (4E) and two junction columns (2E) per pixel.…”
Section: D For Cmsmentioning
confidence: 99%
“…Although no experimental data to validate the simulation results of the guard ring structures exist yet, simulations with the same tools and models were able to predict the experimentally observed breakdown behavior of different devices, namely 3D CMS pixel detectors, with a satisfactory accuracy. 85 V and 110 V, respectively, the corresponding simulated breakdown voltages are 80 V and 95 V [18].…”
mentioning
confidence: 99%